Readiness of Agricultural Human Resources Based on Lokal Wisdom Lumbung Mataraman - Wijaya, Rangga Adi; Dwiatmaja, Christantius; Nugraha, Albert Kriestian Novi Adi; Adi, Priyo Hari (Journal of Ecohumanism, 2024)
The agricultural sector faces challenge of increasing its attractiveness to ensure the sustainability of agricultural human resources. The sustainability model of agricultural human resources emphasizes the resources owned by farmers to develop agricultural businesses into a more realistic approach. The contribution of this study is the development of the Lumbung Mataraman (LM) model as a local wisdom-based HR readiness model that anticipates limitations in the agricultural sector. LM is a local wisdom that has a set of Javanese cultural values to obtain optimal agricultural yields but also at the same time preserves nature. The intervention was carried out as a catalyst for the readiness of agricultural human resources to achieve food self-sufficiency. This research involved farmer groups in the Wonogiri and Sleman districts of Indonesia. The findings show that LM is local wisdom contributes to improving the quality of agricultural human resources in terms of skills, creativity, innovation, and local culture.